Lack of Awareness of the Impact of Improperly Disposed Of Medications and Associated Factors: A Cross-Sectional Survey in Indonesian Households - Alfian, Sofa D.; Insani, Widya N.; Halimah, Eli; Qonita, Nabilla A.; Jannah, Siti S.; Nuraliyah, Nisa M.; Supadmi, Woro; Gatera, Vesara A.; Abdulah, Rizky (Frontiers in Pharmacology, 2021)
Introduction: Disposal of unused medications through environmentally unsafe routes is common In Indonesia. Lack of awareness of the impact of improperly disposed medications is one of the most contributing factor. The objectives of this study were to identify factors associated with lack of awareness of the impact of improperly disposed unused medications and to assess the associations of awareness with medication disposal practices among the general population in Indonesia. Patients and methods: An observational cross-sectional survey was conducted using a non-probability sampling in Bandung, Indonesia from November 2017–January 2018 among respondents aged over 18, have signed informed consent, and were literate. Disposal practices and awareness regarding the impact of improperly disposed unused medications were collected using a pre-validated structured questionnaire. We applied binary logistic regression to assess associations of sociodemographic and other related factors with lack of awareness and report odds ratios (OR) with 95% confidence intervals (CI). Results: Of 497 respondents, more than half of them (53.1%) were not aware that improper medication disposal could harm the environment and population health. Most of respondents (79.5%) never received information about proper medication disposal practices. Education level, number of stored medication at home, and those with previously educated about medication disposal practices were significantly associated with awareness of the proper medication disposal practices. In the multivariate analysis, only those with previously educated about medication disposal practices were less likely to report lack of awareness (OR: 0.043; 95% CI: 0.02–0.09). Conclusion: There is a clear need to increase patient awareness about the importance of proper medication disposal practices. Health care providers can play an important role by educating general population on proper disposal practices.